A Retrospective Clinical Study of Endoscopic Treatment of Carpal Tunnel Syndrome using the Modified Soft Tissue Release kit. Issue 1 (22nd November 2022) - Li, Yiming; Jiao, Xin; Gan, Yaokai; Shi, Dingwei; Wang, Zengguang; Yao, Yifei; Dai, Kerong
Abstract : Objective: Carpal tunnel syndrome (CTS) is the most common peripheral entrapment neuropathy, and endoscopic carpal tunnel release (ECTR) is one of the minimally invasive procedures for the treatment of CTS. Based on the shortcomings of ECTR, we designed the "Modified Soft Tissue Release Kit" to assist the endoscopic operation. This study aimed to evaluate the effectiveness and safety of endoscopic treatment of CTS using this kit. Methods: This retrospective review included 57 patients (86 wrists) who underwent ECTR using the "Modified Soft Tissue Release Kit" at our department between January 2017 and August 2019. Three scale scores (i.e., Quick–Disabilities of the Arm, Shoulder, and Hand [QDASH]; Boston Carpal Tunnel Syndrome Questionnaire [BCTSQ]: symptom severity [BCTSQ‐SS] and functional status [BCTSQ‐FS]) were recorded to assess hand function and symptoms preoperatively, 1 month postoperatively, 3 months postoperatively, and at the last follow‐up. We also asked patients to answer a satisfaction question during follow‐up. Pre‐ and post‐operation scores were compared using paired Wilcoxon signed‐rank test. Spearman's rank‐order correlation was used to evaluate the relationship between scale scores and patient satisfaction. Results: A total of 55 patients (83 wrists) were followed up, with an average follow‐up of 27.2 ± 9.3 months. The median preoperative QDASH score was 45.5; the scores at 1 month postoperatively, 3 months postoperatively, and the last follow‐up were 4.5, 0, and 0, respectively, with a significant decrease noted compared with the preoperative scores ( P  < 0.001). The median preoperative BCTSQ‐SS and BCTSQ‐FS scores were 3.3 and 2.8, respectively; the scores at 1 month postoperatively, 3 months postoperatively, and the last follow‐up were 1.2, 1.0, and 1.0, and 1.1, 1.0, and 1.0, respectively, all of which decreased significantly compared with the preoperative scores ( P  < 0.001). The incidence of nerve injury was 0. The incidence of pillar pain was 0 at the last follow‐up. One patient showed no improvement in hand symptoms and function postoperatively, and two patients showed long‐term recurrence despite postoperative symptom remission. Approximately 94.5% (52/55) of the patients were satisfied or very satisfied with the outcome. Conclusions: ECTR with the "Modified Soft Tissue Release Kit" can significantly relieve symptoms and improve function in patients with CTS, with significant short‐ and mid‐term efficacy and high safety. Abstract : Our team designed the "Modified Soft Tissue Release Kit" for minimally invasive treatment of carpal tunnel syndrome with endoscopy, which had great efficacy and improved the safety of endoscopic carpal tunnel release.